1993
DOI: 10.1007/bf00966771
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of calpain in human lymphoid cells

Abstract: Calpain, a calcium-activated neutral proteinase, is ubiquitously present in human tissues. To determine if lymphoid cells implicated in pathogenesis of demyelination may harbor calpain in a functionally active form, we determined both muCalpain and mCalpain activities in human lymphoid cell lines. DEAE-cellulose and phenylsepharose column chromatography were used to isolate the enzyme from the natural inhibitor, calpastatin. Lymphocytic lines (CCRF-CEM, MOLT-3, MOLT-4, M.R.) showed predominance of muCalpain (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…In contrast, the supernatant of nonactivated THP-1 cells did not degrade myelin, possibly due to a much lower amount of calpain secreted in the extracellular medium, compared with that of activated cells. This finding correlates well with our previous observation that degradation of MBP by calpain is concentration-dependent (Deshpande et al, 1993).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, the supernatant of nonactivated THP-1 cells did not degrade myelin, possibly due to a much lower amount of calpain secreted in the extracellular medium, compared with that of activated cells. This finding correlates well with our previous observation that degradation of MBP by calpain is concentration-dependent (Deshpande et al, 1993).…”
Section: Discussionsupporting
confidence: 93%
“…A large amount (50%) of MBP can be degraded in 1 hr by both isoforms, suggesting that calpains have a strong potential to contribute effectively to demyelination. Increasing amounts of calpain have degraded MBP to greater extents (Deshpande et al, 1993), suggesting that calpain, if produced and secreted locally in large amounts by inflammatory cells in the nervous tissue, may cause degradation of myelin proteins such as that seen in MS or EAE. Degradation of MBP by calpain from other sources (Sato et al, 1982;Chakrabarti and Banik, 1988;Yanagisawa et al, 1988) has been previously demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, stimulation of T cells with these substances causes calpaininduced proteolytic cleavage of PTP-1B, resulting in a 42-kDa enzymatically active form of the phosphatase as a result of C-terminal truncation. Interestingly, PTP-1B can be cleaved by calpain I and calpain II, both of which are present in T cells (37). PTP-1B normally associates with the ER membrane via a C terminus-targeting sequence, whereas the catalytic domain is located near the N terminus (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The role of calpain was examined since all major myelin proteins, including myelin basic protein (MBP) and axonal neurofilament protein (NFP), are substrates of calpain [213, 214]. Activated T-cells also have increased intracellular calcium [215] and express and secrete calpain [216-218]. Using an animal model of MS, experimental allergic encephalitis (EAE), calpain expression was increased twofold over control with decreased levels of myelin associated glycoprotein and NFP [219].…”
Section: Multiple Sclerosismentioning
confidence: 99%